Understanding Key Roles of Two ENSO Modes in Spatiotemporal Diversity of ENSO - Wang, Run; Ren, Hong-Li (Journal of climate, 2020)
El Niño–Southern Oscillation (ENSO) events exhibit a diversity of amplitudes, spatial patterns, and life cycles, with the main ENSO periods concentrated in the 3–7-yr [low-frequency (LF)] and 2–3-yr [quasibiennial (QB)] bands. In this study, the spatiotemporal diversity of ENSO is quantitatively examined by extracting the two ENSO modes, namely, the LF and QB components of ENSO, from the traditional Niño-3.4 index and connecting them with the spatial types of ENSO. El Niño events can be regrouped as the QB-dominated central-Pacific ENSO-like (QB-CP), LF-dominated eastern-Pacific ENSO-like (LF-EP), and LF-dominated mixing (LF-mixing) types. La Niña events with vague spatial patterns can also have the same categorization. The QB-CP and LF-EP El Niño types both have a high-amplitude QB component. Meanwhile, the former is less affected by its powerless LF component, but the latter is controlled by its strong LF component. Ocean dynamics of the two El Niño types are distinct from each other. The thermocline feedback dominates the growth of the two El Niño types and contributes to the phase transition of the LF-EP type, while the zonal advective feedback is of increasing importance in the QB-CP El Niño and mainly contributes to the phase transitions of the two El Niño types. Additionally, the LF-mixing type with ambiguous spatial features and complex life cycles is distinguished from the other two types. These results indicate that the two ENSO modes coexist in the tropical Pacific air–sea system, and their combination with changing amplitude is the key to explaining the spatiotemporal diversity of ENSO.